Managing the Sovereign-Bank Nexus - Dell'Ariccia, Giovanni (Departmental Papers; Departmental Paper ;, 2018)
This paper reviews empirical and theoretical work on the links between banks and their governments (the bank-sovereign nexus). How significant is this nexus? What do we know about it? To what extent is it a source of concern? What is the role of policy intervention? The paper concludes with a review of recent policy proposals.